Fasting modulates GH/IGF-I axis and its regulatory systems in the mammary gland of female mice: Influence of endogenous cortistatin. (15th October 2016) - Villa-Osaba, Alicia; Gahete, Manuel D.; Cordoba-Chacon, José; de Lecea, Luis; Castaño, Justo P.; Luque, Raúl M.
Abstract: Growth hormone (GH) and insulin-like growth factor-I (IGF-I) are essential factors in mammary-gland (MG) development and are altered during fasting. However, no studies have investigated the alterations in the expression of GH/IGF-I and its regulatory systems (somatostatin/cortistatin and ghrelin) in MG during fasting. Therefore, this study was aimed at characterizing the regulation of GH/IGF-I/somatostatin/cortistatin/ghrelin-systems expression in MG of fasted female-mice (compared to fed-controls) and the influence of endogenous-cortistatin (using cortistatin-knockouts). Fasting decreased IGF-I while increased IGF-I/Insulin-receptors expression in MGs. Fasting provoked an increase in GH expression that might be associated to enhanced ghrelin-variants/ghrelin-O-acyl-transferase enzyme expression, while an upregulation of somatostatin-receptors was observed. However, cortistatin-knockouts mice showed a decrease in GH and somatostatin receptor-subtypes expression. Altogether, we demonstrate that GH/IGF-I, somatostatin/cortistatin and ghrelin systems expression is altered in MG during fasting, suggesting a relevant role in coordinating its response to metabolic stress, wherein endogenous cortistatin might be essential for an appropriate response. Highlights: Expression of the GH/IGF-I system is altered in mammary gland of mice during fasting. Fasting altered the expression of somatostatin/cortistatin and ghrelin systems in mice mammary gland. Expression of the components of the ghrelin system correlated with changes in GH/IGF-I during fasting. Endogenous cortistatin seems to be essential for the appropriate response of mammary gland to fasting.